Rural Extension and Technology Transfer as Tools in the Execution of Cultural, Territory and Social Cohesion Appropriation Projects (2023)
The Territorial Approach Development Program (PDET, by its acronym in Spanish) benefits 170 municipalities as a result of the 2016 Peace Agreement between the Colombian Government and the FARC. The program aims to improve the living conditions of the population most affected by conflict, poverty, institutional weakness, and illicit crops. The PDET municipalities were divided into 16 subregions, comprising 11,000 villages and 6.6 million inhabitants. They have a 15-year action plan with over 32,000 initiatives in eight thematic areas: comprehensive rural reform, social participation, reconciliation and coexistence, substitution of illicit crops, infrastructure and land adaptation, social development, environmental reconciliation, and economic development. These initiatives are funded by the government, international cooperation, the private sector, and the Works for Taxes mechanism. For instance, Tumaco, a municipality in the Colombian Pacific, is part of the Sustainable Colombia Program, which includes mangrove restoration projects, regional fruit tree cultivation, and the rehabilitation and production of special cocoa. The National Program for the Promotion of Environmental and Socioeconomic Sustainability in PDET municipalities aims to restore and protect natural capital, improve the income of rural populations through sustainable production projects, and strengthen the technical capacities of local and regional actors. The program is financed with a loan from the IDB and is executed by DAPRE through the Colombia in Peace Fund. In these processes, rural extension and technology transfer are tools that can facilitate the execution of projects for cultural appropriation of the territory and social cohesion, especially in rural areas. These tools aim to promote human and social development, disseminate knowledge, generate opportunities, encourage citizen participation, foster innovation, increase productivity and competitiveness, ensure sustainability and diversification, recognize and value preservation efforts, facilitate exercise and care, manage resources, build trust, promote solidarity and cooperation, foster inclusion, and encourage respect, prevention, and transformation.